Breaking Impasse and Restructuring: The Transformation of Basic Education from Exam Screening to Innovation Empowerment - Teng Wang; Yang Han (Lecture Notes in Education Psychology and Public Media, 2026)
At present, the international competition landscape has undergone profound changes. China is at a critical stage of leapfrogging from technology catch-up development to innovation-led development. This requires basic education to focus on cultivating students' innovation awareness and inquiry ability while strengthening knowledge impartation. However, the current talent cultivation model of basic education cannot meet the needs of social development, which is rooted in the fact that the value orientation of basic education deviates from the education-oriented essence and is narrowed into a tool for hierarchical screening. To cultivate innovative talents, basic education needs to build a diversified evaluation system combining summative assessment and formative assessment, promote the transformation of teaching methods from knowledge cramming to personalized inspiration, and create a school cultural atmosphere that encourages inquiry and embraces diversity.